POTENSI PENINGKATAN PRODUKSI PAKAN DAN KESUBURAN LAHAN SEBAGAI DAMPAK DARI PENANANAMAN HMT PADA LAHAN PINGGIR PEMBATAS TEGALAN DAN KEBUN (STUDI KASUS KECAMATAN GEROKGAK KABUPATEN BULELENG BALI) - Yasa, I M. R.; Adijaya, I N.; Suyasa, I N. (Pastura; Vol 2 No 2DO - 10.24843/Pastura.2013.v02.i02.p11)
The research was carried out from April 2010 – March 2011 to analyze the potential increase of food production and soil fertility as an impact of planting green fodder (HMT) at dry land and gardens boundary of Gerokgak, Buleleng, Bali. The method was using dynamic system approach supported by Participatory Rural Appraisal (PRA) method for identification system. The parameters being analyzed were forage production and potential N addition to soil. The results showed that planting of forage crops interspersed with gamal and lamtoro at 1 (one) meter spacing and underneath them planted with king grass at 0.5 meters as plant boundary of dry land and gardens which potential to increase food production on the average of 83, 1%, or 46 468 tons / year in 2011 and up to 60.754 tons in 2034 compared to the actual production. Besides, planting legume trees (Gliricidia and lamtoro) would be potential to increase nitrogen supply to soil from 83.3 tons up to 91.6 tons.
Keywords: optimizing land boundary, forage production